Utilizing a Cortical Bone Trajectory Pedicle Screw for Lumbar Flexion-Distraction Injury - Naohisa Miyakoshi; Shigeto Maekawa; Masakazu Urayama; Yoichi Shimada (Case Reports in Orthopedics)
Spinal flexion-distraction injuries (FDIs) are unstable fractures, commonly located at the thoracolumbar junction. Management of FDIs often necessitates the use of posterior instrumentation and fusion, but long-segment instrumentation surgery decreases postoperative spinal mobility and increases the risk of junctional kyphosis and fracture. We report the case of a patient with FDI showing an L2 vertebral fracture, unilateral L2 pedicle fracture, and disruptions of the posterior ligamentous complex between L1 and L2. After open reduction using L1 and L2 pedicle screws with a conventional trajectory on the right side, a cortical bone trajectory (CBT) pedicle screw was used as an osteosynthesis screw for the fractured left pedicle. This procedure enabled successful single-level fusion. Follow-up radiological examination revealed good reduction and complete bone union. To the best of our knowledge, utilizing a CBT technique as an osteosynthesis screw in FDIs has not previously been described.